2021
DOI: 10.21037/atm-21-1375
|View full text |Cite|
|
Sign up to set email alerts
|

The effects of a biodegradable Mg-based alloy on the function of VSMCs via immunoregulation of macrophages through Mg-induced responses

Abstract: Background: Restenosis is one of the worst side effects of percutaneous coronary intervention (PCI) due to neointima formation resulting from the excessive proliferation and migration of vascular smooth muscle cells (VSMCs) and continuous inflammation. Biodegradable Mg-based alloy is a promising candidate material because of its good mechanical properties and biocompatibility, and biodegradation of cardiovascular stents.Although studies have shown reduced neointima formation after Mg-based CVS implantation in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 54 publications
0
14
0
Order By: Relevance
“…This low intracellular Ca halts the activation of phagocytic cells and cytokine production which reduces the inflammation [ 130 ]. down-regulate the production of M1-like and up-regulate M2-like macrophage-related cytokines, and as a result, rapid inflammation resolution and tissue repair can occur [ 57 , 131 , 132 ]. Examples of Mg Alloys interaction RS66 alloy (Mg-6.0Zn-1.0Y-0.6Ce-0.6Zr) No acute inflammation [ 133 ].…”
Section: Immune Response Differences Between Degradable and Non-degra...mentioning
confidence: 99%
See 1 more Smart Citation
“…This low intracellular Ca halts the activation of phagocytic cells and cytokine production which reduces the inflammation [ 130 ]. down-regulate the production of M1-like and up-regulate M2-like macrophage-related cytokines, and as a result, rapid inflammation resolution and tissue repair can occur [ 57 , 131 , 132 ]. Examples of Mg Alloys interaction RS66 alloy (Mg-6.0Zn-1.0Y-0.6Ce-0.6Zr) No acute inflammation [ 133 ].…”
Section: Immune Response Differences Between Degradable and Non-degra...mentioning
confidence: 99%
“…down-regulate the production of M1-like and up-regulate M2-like macrophage-related cytokines, and as a result, rapid inflammation resolution and tissue repair can occur [ 57 , 131 , 132 ].…”
Section: Immune Response Differences Between Degradable and Non-degra...mentioning
confidence: 99%
“…The accumulation of lipids and inflammatory cells in the blood vessel wall is the main feature of CAS. Inflammatory cells accumulate in the arterial wall and promote the proliferation and migration of VSMC cells by secreting inflammatory factors and expressing proteins [ 7 9 ]. Previous studies confirmed that the pro-inflammatory properties of IL-1β are related to the development of CAS lesions.…”
Section: Introductionmentioning
confidence: 99%
“…In ammatory cells accumulate in the arterial wall and promote the proliferation and migration of VSMC cells by secreting in ammatory factors and expressing proteins [7][8][9] . Previous studies con rmed that the pro-in ammatory properties of IL-1β are related to the development of CAS lesions.…”
Section: Introductionmentioning
confidence: 99%